Analysis of PV penetration level on low voltage system in Chiang Mai Thailand - Pongsatorn Kerdoum (2020)
© 2019 This paper presents the various levels of photovoltaic (PV) penetration which strongly affect the voltage quality in low voltage systems. The rural area of the Provincial Electricity Authority (PEA) in Chiang Mai is selected as a case study. DIgSILENT PowerFactory program is used to simulate the PV solar rooftop 1-phase on the selected area. This paper analyzes the impact of the PV solar rooftop in various locations and PV penetration levels with the PEA voltage standard. Next, the technical solution by transformer relocation is proposed. The results are compared with the worst case and analyzed the possibility of the solution. The results from the worst case show that only 30% of PV penetration is acceptable in PEA voltage standard and the solution can mitigate the PV penetration level.